Automating the UMP open registration (or) system for course timetabling problem - Kangeswary, Kuppusamy (2013)
The open registration (OR) system is different from the “Program-based Registration System” which allows student to register their academic subject based on their own study plan. UMP’s students are required to make the combination of the study plan to make sure their timetable is suitable with their favorite time. There are some methods on solving the timetabling such as Tabu Search (Qu et al.., 2009), Hill Climbing (Appleby et al 2011), Simulated Annealing (Kirkpatrick and Vecci, 1983) and Great Deluge Algorithm (Dueck,1993) which had been used to solve the college or University timetabling problems. These searching methods fulfilled the automated timetabling system and applied on many systems. These researches will benefit the UMP’s student to view the course information with more specific details and convenience the process course registration online.